Inherited MC1R variants in patients with melanoma are associated with better survival in women. (1st January 2020) - Lira, F.E.; Podlipnik, S.; Potrony, M.; Tell‐Martí, G.; Calbet‐Llopart, N.; Barreiro, A.; Carrera, C.; Malvehy, J.; Puig, S.
Summary: Background: Women have a better melanoma prognosis, and fairer skin/hair colour. The presence of inherited MC1R variants has been associated with a better melanoma prognosis, but its interaction with sex is unknown. Objectives: To evaluate the relationship between germline MC1R status and survival, and determine any association with sex. Methods: This was a cohort study including 1341 patients with melanoma from the Melanoma Unit of the Hospital Clinic of Barcelona, between January 1996 and April 2018. We examined known sex‐related prognosis factors as they relate to features of melanoma and evaluated the sex‐specific role of MC1R in overall and melanoma‐specific survival. Hazard ratios (HRs) were calculated using univariate and multivariate Cox logistic regression. Results: Men showed lower overall survival than women ( P < 0·001) and the presence of inherited MC1R variants was not associated with better survival in our cohort. However, in women the presence of MC1R variants was associated with better overall survival in the multivariate analysis [HR 0·57, 95% confidence interval (CI) 0·38–0·85; P = 0·006] but not in men [HR 1·26, 95% CI 0·89–1·79; P = 0·185 ( P ‐value for interaction 0·004)]. Analysis performed for melanoma‐specific survival showed the same level of significance. Conclusions: Inherited MC1R variants are associated with improved overall survival in women with melanoma but not in men. Intrinsic sex‐dependent features can modify the role of specific genes in melanoma prognosis. We believe that survival studies of patients with melanoma should include analysis by sex and MC1R genotype. What's already known about this topic? Inherited MC1R variants have been associated with a better melanoma prognosis, but their interaction with sex is unknown. What does this study add? MC1R variants are related to better overall survival and melanoma‐specific survival in women but not in men. What is the translational message? These differences between the sexes could imply future changes in melanoma follow‐up and treatment strategies. This provides a basis for understanding the interaction between sex‐related genes and germline variants in cancer.